2017
DOI: 10.18203/2320-6012.ijrms20164443
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of skin diseases in rural population: a cross sectional study at Medchal mandal, Rangareddy district, Telangana, India

Abstract: Background: The skin diseases are affected by various factors. The rural population is more vulnerable because of illiteracy. Therefore an attempt has been made to screen the population of five villages to know pattern of skin diseases. Aims of the study were to assess the prevalence of skin diseases, determine the pattern of skin diseases in the study population in rural community of Medchal mandal and compare previous studies so that inferences can be drawn for the benefit of society. Methods: The study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…A total of 55 cases i.e 53.39% were rendered a definite histopathological diagnosis and 48 cases i.e 46.60% were rendered a diagnosis of dermatitis on histopathological findings. The higher number could be attributed to the higher prevalence of non-infective dermatoses as reported by Bommakanti J. et al [13]…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…A total of 55 cases i.e 53.39% were rendered a definite histopathological diagnosis and 48 cases i.e 46.60% were rendered a diagnosis of dermatitis on histopathological findings. The higher number could be attributed to the higher prevalence of non-infective dermatoses as reported by Bommakanti J. et al [13]…”
Section: Discussionmentioning
confidence: 79%
“…Bommakanti et al in his door to door survey and study of a locality reported that among non-infectious conditions, eczema was the common disease with (182 cases, 15.53%), followed by Pigmentary disorders with (138 cases, 11.77%), other conditions like alopecia areata, seborrheic dermatitis and senile xerosis in (136 cases, 11.60%), Papulosquamous disorders in (109 cases, 9.30%), acne and acneiform dermatoses in (54 cases, 4.61%), polymorphous light eruptions in (50 cases, 4.27%) and bite and stings in (26 cases, 2.22%). Eczemas were found in (58 cases, 4.95%) followed by lichen simplex chronicus in (41 cases, 3.5%) and allergic contact dermatitis in (37 cases, 3.16%) [13] . A total of 4782 histopathological specimens were received in the department of pathology in 3 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation